Review of life cycle assessment on lithium-ion batteries (LIBs) recycling - Domingues, Ana Mariele [UNESP]; Souza, Ricardo Gabbay de [UNESP] (Elsevier, 2024)
The recycling of Lithium-ion batteries (LIBs) waste is recognized as a viable solution for alleviating the pressure on natural resources caused by the increasing demand for materials used in LIBs production and the disposal of these hazardous wastes in landfills. Life Cycle Assessment (LCA) has been widely employed to evaluate the environmental impacts associated with LIBs recycling. However, a comprehensive synthesis of the lessons learned from these assessments, including methodological choices, findings, and implications, is lacking in the literature. Therefore, this study aims to summarize the available knowledge on the application of LCA for LIBs recycling. This study uses a systematic literature review method in combination with structured content analysis to identify and analyze 64 peer-reviewed LCA studies on LIBs recycling. The key findings reveal significant variations in potential impact results and divergent results regarding the environmental preference among the available recycling processes (hydrometallurgical, pyrometallurgical, direct recycling, and bioleaching). These discrepancies arise from different assumptions and methodological choices in LCA, including variations in system boundaries, inputs, the inclusion or exclusion of specific stages, unit process and flows, assumptions regarding the use of avoided products, functional units, impact assessment methods, and the use of secondary data due to the lack of primary data, especially on an industrial scale. While the Climate Change category receives considerable attention, other impact categories are often neglected, making it challenging to establish the environmental preference of a particular recycling technology. For direct recycling and bioleaching technologies lack assessments for all impact categories. Electricity consumption and chemical inputs are identified as hotspots for all recycling options. To enhance the sustainability of LIBs recycling, additional studies that focus on collecting primary data, particularly for the collection, pretreatment, and final disposal stages are recommended. To improve the transparency and reproducibility of future studies, this article provides recommendations and a research agenda for conducting LCA studies in the field of LIBs recycling.